Serum KL‐6 level is a prognostic marker in patients with anti‐MDA5 antibody‐positive dermatomyositis associated with interstitial lung disease. Issue 8 (13th July 2019) - Ye, Yan; Fu, Qiong; Wang, Ran; Guo, Qiang; Bao, Chunde
Abstract: Objective: This study aimed to investigate the clinical significance of Krebs von den Lungen‐6 (KL‐6) serum levels in patients with anti‐MDA5 antibody‐positive dermatomyositis (anti‐MDA5 + DM) having interstitial lung disease (ILD), especially in the amyopathic DM phenotype. Methods: The serum KL‐6 level was measured using a chemiluminescence enzyme immunoassay (CLEIA) in patients with anti‐MDA5 + DM, including clinically amyopathic dermatomyositis (CADM)‐ILD and classic DM‐ILD, and healthy donors. The baseline and post‐treatment serum KL‐6 levels were determined in 39 patients with CADM‐ILD who experienced remission or acute exacerbation. The association between laboratory findings, high‐resolution computed tomography (HRCT) scores, pulmonary function tests (PFTs), and the predictive value of baseline KL‐6 level for death was analyzed. Results: The serum KL‐6 levels were significantly higher in patients with CADM‐ILD (1339 ± 1329 U/mL) compared with DM‐ILD (642.3 ± 498.4 U/mL) and healthy donors (162.4 ± 54.01 U/mL). The KL‐6 levels correlated positively with chest HRCT scores, serum lactate dehydrogenase, serum ferritin levels, and PFTs, but not with erythrocyte sedimentation rate. During follow‐up, the post‐treatment serum KL‐6 levels significantly reduced in the remission/stable group, but increased in the acute exacerbation group. Higher levels of ferritin and KL‐6 and HRCT scores were independently associated with poor prognosis. The 1‐year survival rate was significantly lower in patients with high KL‐6 level than in those with low KL‐6 level. Conclusion: The serum KL‐6 levels may be a useful marker for predicting and monitoring ILD in Chinese patients with anti‐MDA5 + DM, especially amyopathic DM phenotype.